The 100. The complete third season [videorecording (DVD)] - Rothenberg, Jason, 1967- (Warner Bros. Entertainment, 2015)
Reunited with the survivors of the space-station Ark that fell to Earth, Clarke Griffin and her band of juvenile delinquents have faced death at every turn: from a world transformed by radiation to the fierce Grounders who somehow managed to survive it, and the double-dealing Mountain Men from the fortified Mount Weather, whose civilized environment masked a horrible secret.